Carnival forms of suggestion in Ukrainian information space in the context of aconsciousness war - Snytko , Olena (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article examines the carnival forms of suggestion – a widely observed phenomenon on the Internet in Ukraine – in the context of the consciousness war. The carnivalization of consciousness and human existence are considered characteristic features of modern culture, which is also defined by transitivity. Carnivalization is found in various forms of modern culture, in particular, in elite (postmodern), mass and in (youth) counterculture, as well as in all spheres of public life. A systematic, consistent use of the so-called carnival forms of suggestive influence appears a popular phenomenon of the Ukrainian culture of the last several decades. The main carnival mechanism is laughter. This tool plays an important role in self-organization of social life and facilitates the perception of truth. A close study into the countersuggestion means actively used on the Internet in Ukraine during the violent informational and psychological confrontation in 2014-2018 has proven a high effectiveness of the so-called carnival forms. These forms of suggestion, which emerged spontaneously on the Internet during the most difficult months and years of the Russian aggression, played a key role in information protection ensuring and information countermeasures in Ukraine. Having the creolized character and all the signs of a suggestion, these texts have had and continue having a stabilizing effect on the consciousness of individuals improving their emotional intelligence. The carnival forms actualizing these therapeutic countersuggestive texts are organic and effective in the era of crucial worldview changes taking place in the present-day Ukraine. Moreover, the laughter is claimed an effective tool exposing the current political situation, relieving from fear, approving new thoughts and ideas and debunking negative narratives. Furthermore, the suggestive nature of verbal texts organically interacts with audiovisual means of influence and is supported by micro-rhythms of all levels, primarily by lexical, grammatical, and phonetic repetitions, which help to consolidate the primary meanings. Finally, the methods of randomizing ideas, breaking patterns, and creating cognitive dissonance are widely used in the creolized political texts.
Keywords: carnival forms of culture, information space, conspiratorial war, suggestion (suggestion), linguistic mechanisms of suggestion